Proposals for Annual Plan 1966-67 Sectorwise Descriptive Notes Government of Gujarat - Planning Commission (Planning Commission, 1966)
Except for the limited changes dictated by the special needs of the State, the State Plans are expected to follow the broad objectives of the National Plan. Having regard to the special needs of the Gujarat State and keeping in view the broad objectives laid down in the Memorandum on the Fourth Five Year Plan published by the Planning Commission, the draft outline of the Fourth Five Year Plan of Gujarat State involving on outlay of Rs. 501.84 crores was prepared in September, 1965.
Government of Gujarat, General Administration Department